2020
DOI: 10.1177/0300060520927881
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of functional magnetic stimulation in improving upper extremity function after stroke: a randomized, single-blind, controlled study

Abstract: Objective To clarify the efficacy of functional magnetic stimulation (FMS) in improving hemiplegic upper extremity function in patients with sub-acute stroke. Methods In this randomized controlled trial, 40 sub-acute stroke patients with hemiplegia were recruited from inpatient wards in the Department of Rehabilitation and randomly assigned to two groups. In the FMS group, magnetic stimulation was applied to extensor muscle groups of the affected upper extremity. In the low-frequency repetitive transcranial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…So far, rNMS has mainly been studied in adults affected by hemiparesis after stroke. The available evidence demonstrates beneficial effects with regard to muscle tone, strength, motor control, and pain in this cohort [20,39,48,49,54,[64][65][66][67][68][69][70][71][72][73]. Because it is painless and does not require the attachment of electrodes or cables [20,21,25,41,74], rNMS represents an interesting option for pediatric patients, too.…”
Section: Discussionmentioning
confidence: 85%
“…So far, rNMS has mainly been studied in adults affected by hemiparesis after stroke. The available evidence demonstrates beneficial effects with regard to muscle tone, strength, motor control, and pain in this cohort [20,39,48,49,54,[64][65][66][67][68][69][70][71][72][73]. Because it is painless and does not require the attachment of electrodes or cables [20,21,25,41,74], rNMS represents an interesting option for pediatric patients, too.…”
Section: Discussionmentioning
confidence: 85%
“…Litvak's experiment (Litvak et al, 2007) proved that magnetic stimulation of muscles or peripheral nerves can help the upper limb motor function recovery of stroke patients by promoting the plasticity change of M1 region and providing sensory input. The study of Chen et al (2020) proved that PMS can improve the Fugl-Meyer score and Barthel index of upper limbs in stroke patients, and the efficacy is superior to LF-RTMS. Struppler et al (2007) study on eight patients with mild paralysis after focal cerebral ischemia found that after repeated PMS, the recovery of hand function and the decrease of spasticity were related to the significant increase of neural activation within the superior posterior parietal lobe and the premotor cortex areas.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, in this study, a parabolic coil was adopted over the left M1, which could stimulate the SMA at the same time to enhance the therapeutic effect. The parabolic coil was often used peripherally to improve swallowing and respiratory and motor function after stroke [13][14][15]. However, to our knowledge, this is the rst description of poststroke hemichorea treated with rTMS by a parabolic coil.…”
Section: Discussionmentioning
confidence: 98%